KEPUASAN PASIEN DAN MINAT MEMANFAATKAN KEMBALI JASA PELAYANAN KESEHATAN DI PUSKESMAS KANDANG KOTA BENGKULU - Susilo Wulan; Desliana Desliana (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Puskesmas as the first-level provider of health services belonging to the government must prioritize the provision of quality health services, affordable, fair and equitable. The quality of good health services will create patient satisfaction and loyalty. The purpose of this study was to study the Relationship of Patient Satisfaction with Interest in Reusing Health Service in Puskesmas Kandang Kota Bengkulu.Is an analytic survey research using Cross Sectional approach. The population of this study were all the patients who visited and recorded in the register book pukesmas Kandang town Bengkulu August 2016. Sampling technique using Accidental Sampling. Measurement of patient satisfaction and interest in reusing health care services was measured using a questionnaire. Data analysis using univariate test, bivariate test using chi square test (χ2). Results From 54 patients who came to Puskesmas Kandang there were Patients who were satisfied with the health service at Puskesmas Kandang Kota Bengkulu as many as 34 patients (63.0%), Patients interested in reusing health services at Bengkulu City Kandang Community Health Center as many as 38 people patients (70.4%). There is a significant correlation between patient satisfaction and interest in re-utilizing health service in Puskesmas Kandang Kota Bengkulu with medium category. Keywords: health service, interest, patient satisfaction